Cartas de Arguedas a Abelardo Oquendo en el Archivo Arguedas de la PUCP - Pinilla Cisneros, Carmen María (2011)
Four letters are included in this publication that Jose Maria Arguedas addressed to Abelardo Oquendo. They document Arguedas’ interest in choosing persons of great literary talent and solid judgemente as editors for his writings. These letters also reveal his personal interpretation of certain practices of Lima intellectual groups, as well as his committed defense in protecting the authenticity of artistic expressions of the Andean world.